Aggrecan modulates the expression and phosphorylation of tau in a novel bigenic TauP301L ‐ Acan mouse model. (17th August 2020) - Schmidt, Sophie; Stapf, Caroline; Schmutzler, Sandra; Lachmann, Ingolf; Arendt, Thomas; Holzer, Max; Sonntag, Mandy; Morawski, Markus
Abstract: Selected types of neurons in the central nervous system are associated with a specialized form of extracellular matrix. These so‐called perineuronal nets (PNs) are supramolecular structures surrounding neuronal somata, proximal dendrites and axon initial segments. PNs are involved in the regulation of plasticity and synaptic physiology. In addition, PNs were proposed to carry neuroprotective functions as PN‐ensheathed neurons are mostly spared of tau pathology in brains of Alzheimer patients. Recently, the neuroprotective action of PNs was confirmed experimentally, demonstrating (i) that mainly aggrecan mediates the neuroprotective function of PNs and (ii) that aggrecan seems to generate an external shielding preventing the internalization of pathological forms of tau. In the present study, we aimed at extending these findings and hypothesized that aggrecan further provides an intracellular protection by preventing mutation‐triggered formation of pathological forms of tau. We used crossbreds of TauP301L mice and heterozygous aggrecan mice which are characterized by spontaneous deletion of the aggrecan allele. We analysed the extent of tau pathology in dependence of aggrecan protein amount by applying immunohistochemistry, Western blotting and ELISA. The results clearly indicate that aggrecan has no significant impact on tau aggregation in the brainstem of our mouse model. Still, reduced aggrecan levels were accompanied by increased levels of tau protein and reduced number of Tau‐1‐positive neurons, which indicate an increase in phosphorylation of tau. In conclusion, these data demonstrate a correlation between aggrecan and P301L mutation‐triggered tau expression and phosphorylation in our bigenic mouse model. Abstract : Perineuronal nets (PNs) are the most obvious manifestation of extracellular matrices in the brain. PNs carry neuroprotective functions as PN‐ensheathed neurons are spared of tau pathology. To investigate the proposed association between PNs and Alzheimer's disease, we generated a bigenic mouse model of TauP301L mice and heterozygous aggrecan mice. Our results highlight a correlation between aggrecan and P301L mutation triggered tau expression and phosphorylation in our bigenic mouse model.